Immunotherapy in Acute Myeloid Leukemia: Where We Stand - Isidori, Alessandro; Cerchione, Claudio; Daver, Naval; DiNardo, Courtney; Garcia-Manero, Guillermo; Konopleva, Marina; Jabbour, Elias; Ravandi, Farhad; Kadia, Tapan; Burguera, Adolfo de la Fuente; Romano, Alessandra; Loscocco, Federica; et al. (Frontiers in Oncology, 2021)
In the past few years, our improved knowledge of acute myeloid leukemia (AML) pathogenesis has led to the accelerated discovery of new drugs and the development of innovative therapeutic approaches. The role of the immune system in AML development, growth and recurrence has gained increasing interest. A better understanding of immunological escape and systemic tolerance induced by AML blasts has been achieved. The extraordinary successes of immune therapies that harness the power of T cells in solid tumors and certain hematological malignancies have provided new stimuli in this area of research. Accordingly, major efforts have been made to develop immune therapies for the treatment of AML patients. The persistence of leukemia stem cells, representing the most relevant cause of relapse, even after allogeneic stem cell transplant (allo-SCT), remains a major hurdle in the path to cure for AML patients. Several clinical trials with immune-based therapies are currently ongoing in the frontline, relapsed/refractory, post-allo-SCT and minimal residual disease/maintenance setting, with the aim to improve survival of AML patients. This review summarizes the available data with immune-based therapeutic modalities such as monoclonal antibodies (naked and conjugated), T cell engagers, adoptive T-cell therapy, adoptive-NK therapy, checkpoint blockade via PD-1/PD-L1, CTLA4, TIM3 and macrophage checkpoint blockade via the CD47/SIRPa axis, and leukemia vaccines. Combining clinical results with biological immunological findings, possibly coupled with the discovery of biomarkers predictive for response, will hopefully allow us to determine the best approaches to immunotherapy in AML.